PENGEMBANGAN UMKM SCALLING UP USAHA MAKANAN DI DESA BAYONGBONG - Sukirno, Sukirno; Algifari, M.; Ramadhan, Dikri; Ramadani, Arfah; Alfarisi, Muhammad Tsalman; Hermawan, Dede; Sopyan, Alif Wahyu; Hidayat, Danih Jian; Fathur Rohman, Muhammad Iqbal; Madani, M Fikri Haikal; Andriani, Rani; Fisimar, Farhan Al; Fauzi, Habal; Fauziah, Rizkia; Septiani, Septiani; Nijar, Afnan Farhan; Hakim, Mizanul; Ramadhan, Risan; Maolana, Ikhsan; Nursaadah, Siti; Triguna, M Ivan (Jurnal PkM MIFTEK, 2024)
The position of Micro, Small and Medium Enterprises (MSMEs) in the national economy has an important and strategic role. This condition is very possible because the existence of MSMEs is quite dominant in the Indonesian economy, due to the large number of industries and in every economic sector; great potential in employment, and the contribution of MSMEs in the formation of Gross Domestic Product (GDP) is very dominant. Therefore, through this Community Service Program (KKN), Group 7 KKN conducted training and mentoring for Micro, Small and Medium Enterprises in Bayongbong Village for 1 month. With the aim of helping and providing an understanding of how very influential branding and packaging design are in marketing products in the market. As for the results achieved by Micro, Small and Medium Enterprises, their products will have branding, product logos and packaging designs.